2022
DOI: 10.1111/jcpp.13614
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐year longitudinal birth cohort study of individuals diagnosed with autism spectrum disorder before seven years of age

Abstract: Background: Previous longitudinal studies have demonstrated that psychosocial outcomes for autistic adults are very limited. However, most studies are clinic-based and liable to selection bias and major methodological problems. Methods: We conducted a long-term follow-up study with 278 autistic individuals from our previous birth cohort study comprising 31,426 individuals. All participants were born in northern Yokohama between 1988 and 1996, diagnosed with autism spectrum disorder (ASD) by age seven, and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Using the Howlin definition for an overall social outcome, ‘good’ or ‘very good’ outcomes were recorded for almost half of participants (49%), over double the rate (20%) reported in systematic reviews of studies mostly conducted in clinical populations, or historic cohorts conducted when diagnostic criteria were narrower or when diagnosis were less likely in people without co‐occurring intellectual disabilities (Mason et al, 2021 ; Steinhausen et al, 2016 ). The rate of good or very good outcomes in SNAP is more comparable to a recent population based study conducted in Japan (Iwasa et al, 2022 ) which found 38% of autistic people diagnosed prior to age seven to have ‘very good’ or ‘good’ outcomes. This suggests that while autistic people face considerable difficulties, previous findings may overestimate their challenges.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using the Howlin definition for an overall social outcome, ‘good’ or ‘very good’ outcomes were recorded for almost half of participants (49%), over double the rate (20%) reported in systematic reviews of studies mostly conducted in clinical populations, or historic cohorts conducted when diagnostic criteria were narrower or when diagnosis were less likely in people without co‐occurring intellectual disabilities (Mason et al, 2021 ; Steinhausen et al, 2016 ). The rate of good or very good outcomes in SNAP is more comparable to a recent population based study conducted in Japan (Iwasa et al, 2022 ) which found 38% of autistic people diagnosed prior to age seven to have ‘very good’ or ‘good’ outcomes. This suggests that while autistic people face considerable difficulties, previous findings may overestimate their challenges.…”
Section: Discussionsupporting
confidence: 81%
“…Prior to this study, a single population based cohort has reported outcomes in adulthood. The Yokohama Longitudinal ASD Birth Cohort (Y‐LABiC) (Iwasa et al, 2022 ) reported outcomes from autistic participants in a Japanese population cohort. While their findings indicated high levels of support needs, low levels of friendship, and challenges in employment and education, these challenges were not as great as had been reported in previous systematic reviews (Mason et al, 2021 ; Steinhausen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in unsupported employment settings, there may be greater pressure to conform to neurotypical norms. This explanation is plausible since there are higher rates of unemployment and supported employment, and lower rates of unsupported employment, amongst autistic adults in Japan [ 142 ] than Australia and the USA (i.e., where we found group differences [ 143 , 144 ]). As such, the autistic participants in Japan may not need to camouflage their autistic traits as much to fit in to their specific workplace environments (and therefore may report lower camouflaging).…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, they were asked to complete the PEM-CY and Kid-& Kiddo-KINDL Parents' Version (KINDL) questionnaires if they agreed to participate in the study. Given the impact of participation status on psychosocial outcomes in children with NDDs [10], KINDL was used to determine the quality of life of the participants. The questionnaires were filled out in person with paper and pen when they visited the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…This rate was 30.6% among children with ASD without intellectual disabilities [9]. Moreover, the psychosocial outcomes were "poor" for 25.6% and "very poor" for 4.8% (based on a five-level classification ranging from very good to very poor) [10]. The most common reason for school refusal among children with ASD has been found to be bullying [11].…”
Section: Introductionmentioning
confidence: 99%